Production of biodiesel from palm oil - Adnan, Mohd Ramadan Syawal; Zawawi, Muhammad Zul Hilmi; Izaham, Muhammad Izzuddin; Sharip, Norazreen (Penerbit UTHM, 2020)
The present researches study the alternative fuel to replace the diesel fuel and how to produce the alternative fuel. Diesel fuel which is made from fossil fuel due the anaerobic decomposition through million years cause many harmful effect to the environment and human health such as the greenhouse effect, air pollution, acidification and more. The aim of the study is to produce the biodiesel from vegetable oil which is palm oil. It starts with mixing the 50 ml of ethanol and 0.5 g of sodium hydroxide as catalyst. The dissolved catalyst then will be poured into the heated 250 ml of palm oil and be stirred for 30 minutes. After the content is mixed the transesterification method is carried out. The content then transferred to separating funnel for separating process. At the end, two layers which the bottom layer will be by- product and the upper layer will be biodiesel. The biodiesel will enter purification method which rinse it with hot distilled water and ready to be test which are the density, kinematic viscosity and heating value of the biodiesel. By using biodiesel as an alternative fuel, the environment and human health will be secure more and it may attract people to more concern about the benefits of the biodiesel.